2020
DOI: 10.37303/psikovidya.v23i2.147
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kontrol Diri Dengan Smartphone Addiction Pada Mahasiswa Pengguna Smartphone Di Program Studi S1 Teknik Elektro Universitas Negeri Malang

Abstract: Penelitian ini bertujuan untuk mengetahui hubungan antara kontrol diri dengan Smartphone Addiction pada mahasiswa pengguna Smartphone di program studi strata 1 Teknik Elektro Universitas Negeri Malang. Penelitian merupakan penelitian kuantitatif dengan populasi 297 dan responden yang diambil berjumlah 171 mahasiswa Teknik Elektro Universitas Negeri Malang yang dipilih menggunakan teknik Purposive sampling. Instrumen penelitian yaitu Smartphone Addiction scale dengan 32  pernyataan  dan  skala kontrol diri yang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…This research includes internal factors, namely self-control from I-PACE model. The decisive factor in determining the propensity for smartphone addiction was individual's choice of self-control (Adiyatma et al, 2020;Anzani et al, 2019;Chotpitayasunondh & Douglas, 2018;Li et al, 2021). Self-control is the ability to replace or change individual's psychological response and refrain from carrying out undesirable behavior (Baumeister et al, 2007).…”
Section: Self-control and Smartphone Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research includes internal factors, namely self-control from I-PACE model. The decisive factor in determining the propensity for smartphone addiction was individual's choice of self-control (Adiyatma et al, 2020;Anzani et al, 2019;Chotpitayasunondh & Douglas, 2018;Li et al, 2021). Self-control is the ability to replace or change individual's psychological response and refrain from carrying out undesirable behavior (Baumeister et al, 2007).…”
Section: Self-control and Smartphone Addictionmentioning
confidence: 99%
“…FOMO factor was selected as an internal factor related to technological developments and plays an important role in worsening smartphone addiction (Elhai et al, 2018;Elhai, et al, 2021;Servidio, 2019;Traş & Öztemel, 2019). This research includes self-control factor to determine smartphone addiction in adolescents (Adiyatma et al, 2020;Anzani et al, 2019;Chotpitayasunondh & Douglas, 2018;Li et al, 2021) using Structural Equation Modeling (SEM) analysis method.…”
Section: Research Noveltymentioning
confidence: 99%
“…Hubungan antara Academic Stress dengan Smartphone Addiction pada mahasiswa pengguna smartphone menunjukkan karena menggunakan smartphone sebagai copying stress [17]. Korelasi negatif atau hubungan negatif yang signifikan antara kontrol diri dan Smartphone Addiction pada mahasiswa semakin tinggi kontrol diri individu.…”
Section: Pendahuluanunclassified
“…Based on a survey on smartphone use found that 56.2 percent or about half of the population in Indonesia used smartphones in 2018, including students who use it (Gustilawati et al 2020). Students who use smartphones certainly have a reason, including as a life style and a support for their lives (Anzani et al 2020;Pebriani, 2019;Syifa, 2020).…”
Section: Introductionmentioning
confidence: 99%